Viral Glomerulopathy - Margaret Deoliveira; Hridyesh Sikri; Samuel Mon-Wei Yu; John Cijiang He (Glomerular Diseases, 2023)
Background: The association between viral infections and glomerular diseases, commonly known as “viral glomerulopathies,” has been described in various clinical scenarios for decades. Despite advancements in diagnostic tools, it remains challenging to establish a causative link fully. Summary: Data from mouse models have substantiated clinical observations and implicate direct viral infection in the pathogenesis of viral glomerulopathy, particularly in human immunodeficiency virus-associated nephropathy. In addition to the traditional concept of direct viral effects on kidneys, other factors such as APOL1 risk alleles can further modify the clinical outcomes or presentations of different viral glomerulopathies. Newly developed antiviral drugs are now applicable to a wider range of patients with lower kidney function and fewer side effects. Key Message: Efforts focusing on vaccines and antiviral treatments have significantly reduced the incidence of viral glomerulopathies. However, the most recent pandemic caused by severe acute respiratory syndrome coronavirus 2 infection complicated by COVID-associated nephropathy illustrates our susceptibility to novel viruses. Ongoing research is pivotal to deciphering the mechanisms behind viral glomerulopathies and discovering therapeutics in a collaborative approach.